Nature et culture dans la liste du patrimoine mondial : l’expérience de Rio de Janeiro - Rafael Winter Ribeiro (VertigO, 2013)
The objective of this study is to analyze the relationship between nature and culture in the Unesco World Heritage List based on the Rio de Janeiro application to the cultural landscape category. The city application had become an excellent laboratory for many reflections on the relationships between nature, culture, heritage and the images produced in this process. Rio’s bid also allows thinking over how appropriate is the Unesco Cultural Landscape category, identified as being associated with a strong presence of so-called natural elements, even if they had been worked by man. We observe the inclusion of urban landscapes in this category as a great embarrassment, since they are, according most branches of geography, the best definitions of cultural landscape, which is understood as the landscape changed by men. Two main traditions can be labeled in accordance with how the category of Cultural Landscape is used in the designated sites : one is strongly associated with landscape design, and another is similar to the Vidal de la Blache’s concept, in which the relationship between man and his environment is emphasized, and runs especially by facilitating the registration of sites associated to traditional lifestyles. The image of Rio de Janeiro that emerges from the application to adapt to this model is that of a city linked to the modern movement, in which the great works on coastal landscapes and the mountains reforestation had a fundamental importance.